Analysis of Brand Preference of Soft Drinks among Urbanites in Punjab - Mahajan, Rajesh; Gupta, Binoo; Khanna, Seema (Indian Journal of Marketing, 2005)
Brands occupy a particular niche in consumer mind. Powerful brands influence consumer so much that it becomes difficult for them to shift their preference to other product, Coca-Cola, Pepsi, Limca, Fanta, Maaza are powerful brands in soft drinks industry. These brands enjoy high brand equity. In 2003 the Cola’s turned into weapons of mass destruction as according to study of Centre for Science and Environment (CSE) reported that level of pesticides in Coke was thirty times more and in case of its rival Pepsi it was thirty five times more than the levels stipulated by European Economic Commission norms. In this regard two studies has been conducted to know about firstly, the brand preference of soft drinks among urbanites in Punjab and secondly to know whether Ban on soft drinks had any effect on the consumer brand loyalty.